REVITALIZATION OF THE INDONESIAN POSTAL MUSEUM WEBSITE THROUGH THE DESIGN THINKING APPROACH - Nabila Febriyulisky; Didit Adwiyatmoko Soewardikoen; Hanif Azhar; Yanuar Rahman; Andreas Rio Adriyanto (Adisam Publisher, 2025)
The Indonesian Postal Museum is facing challenges in attracting the attention of younger generations. The purpose of this study is to create an interactive website based on artificial intelligence (AI) that maximizes the user's digital experience. This method will use Design Thinking Approach. Empathize, define, ideate, prototype, and test those the five steps in this approach, which uses a qualitative descriptive approach. To collect data, observation, interviews, questionnaires, and literature review were employed. The research findings indicate that the use of AI features such as chatbots, content personalization, and other interactive components can enhance user engagement online and encourage them to visit the museum in person. It is hoped that this project will serve as a model for digital revitalization for other museums in Indonesia